Effects of treatment with local anesthetics on RANKL expression in MG63 and PDL cells - Tsui-Hsein Huang; Chien-Wei Chao; Chia-Tze Kao (Elsevier, 2021)
Background/purpose: Local anesthesia (LA) application is a routine dental work in clinic. The aim of present study was to evaluate the extent of biologic effects of LA on periodontal ligaments (PDL) or bone cells (MG63). Materials and methods: Local anesthetics (LAs) at different concentrations were added to PDL and MG 63 cells. The viability of the cells was analyzed using an MTT assay. The inflammatory markers, COX-2, IL-1, IL-6 and TNF-A, of PDL and MG63 cells treated with LAs were analyzed with a Western blot assay. The extract medium of the LA-treated PDL cells was added to the MG63 cells for subsequent culture and to examine the RANKL, ALP, and OPG expression. The data were statistically analyzed with p < 0.05 set as an indication of significance. Results: The viability of the PDL and MG63 cells was less 50% at LAs concentrations above the 10 mM. At high LA concentrations, the PDL and MG63 cells treated with LAs became spherical in shape, or vesicles developed in the cytoplasm. The IL-1, IL-6, and TNF-A expression in the PDL groups showed no statistical differences between Septanest and Scandonest (p > 0.05). The RANKL expression in the MG63 cells increased as the Septanest and Scandonest concentrations were increased in the PDL extract medium (p < 0.05) after 48 h of culturing. Conclusion: The LAs with adrenaline increased inflammation in the PDL and MG63 cells. The LA-treated PDL extract medium increased the RANKL expression in the MG63 cells.